Dual coating strategy of CoS2@Co@C toward fast insertion/extraction anode material for sodium‐ion batteries. (14th November 2020) - Abubshait, Haya A.; Alshahrani, Thamraa; Alhashim, Hala H.; Flemban, Tahani H.; Ali, Ghulam; Mahmood, Qasim; Laref, Amel; Kattan, Nessrin A
Summary: Rechargeable sodium‐ion batteries are facing the challenge of highly electrochemical active anode for their realization. In this study, we report a dual coating strategy of CoS2 with metallic Co particles and carbon to boost the charge transfer and stability. The phase of CoS2 and the existence of Co metallic particles were confirmed using x‐ray diffraction (XRD). x‐ray photoelectron spectroscopy (XPS) results corroborate the presence of carbon and CoS bonding. The prepared CoS2 @Co@C anode reveals high performance where it shows a capacity of 712 mA h g −1 at 0.05 C rate. The CoS2 @Co@C electrode exhibits exceptional high rate capability where it exhibits a capacity of 260 mA h g −1 at elevated rate of 10.0 C. The cyclability of CoS2 @Co@C anode is tested at 0.05 C and 0.5 C rates where the electrode shows 78% and 45% capacity retention of stabilized capacity. The reaction mechanism of the CoS2 @Co@C electrode is determined using x‐ray absorption spectroscopy (XAS) and the results show reversibility of the material. Abstract : A duel coated CoS2 @Co@C exhibited high rate capability as anode for sodium‐ion batteries with reversible sodium insertion/extraction.